The most beautiful gift - Snow, Jonathan (New York : Warner Books, 1996)
Enraptured when he sees his first snowflake just before Christmas, Mark, a seven-year-old boy living in Italy, searches for just the right person to give the treasure he has saved.
Keywords: Christmas stories; Snowflakes -- Fiction; Christmas -- Fiction; Snow -- Fiction; Grandfathers -- Fiction